Resepsi Audiens Terhadap Citra Negatif Islam Dalam Film Taken 2 - Dwi Cahyadi, Bara, Agus Triyono, S.Sos, M.Si, Fajar Junaedi, M.Si (2015)
A film usually appears as a picture or a social phenomenon in which it can be public attention. Currently being crowded and always raised in the film is about Islam. islam as a religion a emerged with the teachings and noble behavior even have a negative stigma of Western society. Not the least of the Western-themed films Islam, but Islam have got begtive position. Judging from the role - a role that is found in the film. As in the movie Taken 2, Islam is described by a set of sellers woman cruel and have no mercy. By usinmg the method of analysis of audience reception, the message by using a background media audinece in the form of experience, education and social status. The result of a study involving four respondents who have been based on age, religion, and educationand conducted by interview separately concluded that all respondents are in oppositional position, they reject all violence committed by Muslims in this movie because it does not fit with the experience they experience when interacting with Muslims around the. Islam in the movie Taken 2 is different from the Islam in their daily lives.